RAFT polymerisation of N-vinylformamide and the corresponding double hydrophilic block copolymers. Issue 44 (25th October 2022) - Dupre–Demorsy, Alexis; Kurowska, Izabela; Balayssac, Stéphane; Hennetier, Marie; Ric, Audrey; Bourdon, Valérie; Ando, Tsuyoshi; Ajiro, Hiroharu; Coutelier, Olivier; Destarac, Mathias
Abstract : Polyvinylamine-based double hydrophilic block copolymers are synthesised from RAFT polymerisation of N -vinylformamide. Abstract : Reversible addition–fragmentation chain transfer (RAFT) homopolymerisation of N -vinylformamide (NVF) is reported for the first time. Reactions were conducted in DMSO at 35 °C using a xanthate RAFT agent. PNVFs of predetermined molar masses up to M n ∼ 80 000 g mol −1 and low dispersities (<1.4) were synthesized. Excellent chain-end fidelity was confirmed by ESI-TOF mass spectrometry. A series of double hydrophilic block copolymers comprising a PNVF segment were successfully synthesized and characterized via asymmetric flow field flow fractionation (AF4) and 1 H DOSY-NMR techniques. Finally, poly( N -vinylcaprolactam)- b -poly( N -vinylformamide) (PVCL- b -PNVF) was hydrolysed into the original dual responsive poly( N -vinylcaprolactam)- b -poly( N -vinylamine) (PVCL- b -PVAm), thus revealing the strong potential of this RAFT approach to develop PVAm-based complex architectures.